Effect of Diazepam on Thyroid Function Hormone and Associated Histological Markers - Michelle, Ogidiagba Stephanie; Gamde, Solomon Matthias; William, Bitty; Kabir, Hauwa (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Diazepam is widely used to manage anxiety and depression, but its effect on thyroid function remain poorly understood. This study aimed to explore the potential effects of diazepam on thyroid function hormones (T3, T4, and TSH), lipid profile, glucose, cortisol levels and thyroid gland histology in animal models. Twenty-four pre-pubertal rats (average weight 160g ± 20g) were divided into four groups, receiving diazepam at 15 mg/kg, 30 mg/kg, or 60 mg/kg daily for seven days, while a control group received standard feed and water ad libitum. General health, including body weight, food and water intake, and behaviour, was monitored. Animals was euthanized, the thyroid glands were analysed histologically, and serum levels of T3, T4, TSH, cholesterol, triglycerides, HDL, LDL, glucose, and cortisol were measured. No statistical significant differences were found across groups (p > 0.05), though trends suggested dose-dependent effects. TSH levels were slightly elevated in the intermediate (at 30 mg/kg) and high-dose groups (at 60 mg/kg), with a minor T4 increase at 30 mg/kg. Triglycerides showed high variability, significantly increasing in the low-dose group (at 15 mg/kg). Histological analysis showed no major thyroid abnormalities. While diazepam does not significantly disrupt thyroid function or metabolism, subtle dose-related effects warrant further clinical investigation.